(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
This study investigated the impact of flood on groundwater quality in Nguru, Yobe State. The electrical resistivity survey delineated five geologic layers which includes topsoil, clay, sand, sandy clay and sand. The third and the fifth layers in the study area constitute the aquifers. The first aquifer is semi-confined and it is highly prone to contamination from flood. The second aquifer is confined and it is the most reliable for potable water. The hydrochemical analysis of the groundwater revealed that the groundwater in the study area has elevated concentrations of Arsenic, Iron, Cadmium, and Lead during both wet and dry seasons. The concentration of these metals in the water samples exceeded the WHO permissible limits. The Chromium level in the groundwater is slightly moderate. In general, the groundwater in the study area is considered not fit for consumption except if treated. It is therefore recommended that the consumption of water from shallow boreholes and hand dug wells in the study area should be discouraged and boreholes for domestic water consumption should be drilled to a depth of 80 m within the second aquifer.